Study of market supply statistics in trading of hops - Pavlovič, Martin (Hmeljarski bilten, 2022)
The International Hop Growers’ Convention (IHGC), is the only international body representing the interests of members of the hop industry from around the globe. Part of its duties within its Economic Committee are to report data from 21 hop producing countries three times each year. Data collection methods and methods unique to the U.S. and Germany are discussed. The U.S. and Germany produced 40.18 and 33.74 percent of the world's hop acreage respectively in 2020. The balance of global acreage (i.e. 26 percent of total global acreage) was divided by 19 producing countries. Reporting methods are demonstrated and data unique to the IHGC is highlighted. The qualitative value of the organization to the industry is also revealed.
Keywords: alfa-kisline; alpha-acids; analiza trga; cene; hmelj; hops; IHGC; market analysis; parametri ponudbe; prices; supply parameters